DEVELOPING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH DIRECTED READING-THINKING ACTIVITY STRATEGY - Oktaviana, Lusi; Rufinus, Albert; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research answers the problem that is, the use of directed reading thinking activity strategy improves students’ reading comprehension on narrative text of the eighth grade of SMP N 2 Pontianak. This study was conducted to answer the following problems:How does directed reading-thinking activity improve students’ reading comprehension in the orientation, complication and resolution in narrative text?In this research, direct reading thinking strategy is reading strategy in which focused on developing the students reading comprehension in finding out the main idea and the detailed information and understanding the reference, inference and the new or unknown vocabularies of narrative text. This study used classroom action research method. The tools of data collection used observation checklist, and field note. On the first, second and the third cycle the writer used picture and text as helping strategy. From the result of measurement test, the data showed that the students’ mean score had improvement from the first cycle to the third cycle. The research results showed that students’ reading comprehension on narrative text improved after being taught by Directed Reading-Thinking Activity Strategy. Keyword: Reading Comprehension, Narrative Text, and Direct Thinking Activity Strategy. Abstrak: Penelitian ini menjawab masalah mengenai penggunaan strategi membaca cermat secara langsung dalam meningkatkan pemahaman membaca pada teks narrative terhadap siswa kelas delapan di SMP Negeri 2 Pontianak . studi ini untuk menjawab permasalah berikut: bagaimana strategi membaca cermat secara langsung dapat meningkatkan kemampuan pemahaman membaca siswa melalui orientasi,complikasi dan resolusi pada teks naratif. Dalam penelitian ini direct reading thinking activity strategi adalah strategi membaca yang mana berfokus dalam meningkatkan pemahaman membaca siswa dalam menemukan ide pokok, infornasi terperinci, referensi, kesimpulan dan kosa kata baru pada teks naratif. Studi ini menggunakan metode penelitian tindakan kelas. Alat pengumpulan data menggunakan observasi centang dan halaman catatan. Dalam siklus pertama, kedua dan ketiga penulis menggunakan gambar dan teks sebagai membantu tekhnik tersebut. Dari hasil tes penilaian, data menunjukkan bahwa nilai rata –rata siswa mengalami peningkatan dari siklus pertama hingga siklus ketiga. Dari hasil analisis data menunjukkan pemahaman membaca siswa pada teks naratif menggunakan direct reading thinking activity strategy meningkat. Kata kunci : Pemahaman Membaca, Teks Naratif, dan Strategi Membaca Cermat Secara Langsung.